Students’ Language Skills Development through Short Stories - Arias, Gladis Leonor (Íkala, Revista de Lenguaje y Cultura, 2017)
The purpose of this article is to share with English teachers the findings of a research project whose main goal was to describe the impact of developing students’ linguistic competence through listening and reading short stories. It was carried out among third-semester students at Universidad Santo Tomás Tunja (USTA). The main theoretical aspects that support this study are: English teaching and literature, teaching English through short stories, and encouraging student speaking by using short stories. The study was carried out within the framework of collaborative action research. Hence, the instruments used to gather information were: student artifacts (written compositions and oral reports), the teacher’s journal, and a survey. Some of the most important findings were: that students showed a significant gain in vocabulary and expressions through reading and listening; that reading was useful for improving their oral competence; and that the students’ exposure to the target language engaged them to improve their language acquisition and practice. This research also fostered students’ awareness of literature.